The Influence of Motivation Achievement, Training, and Self-Efficacy on Public Employee Performance - Arvan, Danti; Afriyeni, Afriyeni (LifeSciFi, 2025)
Performance problems in this agency are reflected in the low achievement of work targets, limited innovation, and weak teamwork. These challenges are particularly critical for the Padang City Fisheries and Food Service, which has a strategic role in supporting food security and improving fishermen’s welfare. This study aims to analyze the influence of achievement motivation, education and training, and self-efficacy on employee performance at the Padang City Fisheries and Food Service. This study uses a quantitative approach with a survey method of 30 respondents who were selected at random and simple. The data were analyzed using multiple linear regression with classical validity, reliability, and assumption tests to ensure the reliability of the model. The results of the study showed that achievement motivation and training had a positive and significant influence on employee performance, while self-efficacy had no significant effect. Simultaneously, the three independent variables contribute to improved performance. These findings provide practical implications for human resource management in the public sector, especially in designing performance improvement policies through strengthening intrinsic motivation and implementing training oriented to the needs of the position.